2009
DOI: 10.1371/journal.pone.0007119
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Allogenicity of Mesenchymal Stem Cells in Engraftment and Wound Healing in Mice

Abstract: Studies have shown that allogeneic (allo-) bone marrow derived mesenchymal stem cells (BM-MSCs) may enhance tissue repair/regeneration. However, recent studies suggest that immune rejection may occur to allo-MSCs leading to reduced engraftment. In this study, we compared allo-BM-MSCs with syngeneic BM-MSCs or allo-fibroblasts in engraftment and effect in wound healing. Equal numbers of GFP-expressing allo-BM-MSCs, syngeneic BM-MSCs or allo-fibroblasts were implanted into excisional wounds in GFP-negative mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
136
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(143 citation statements)
references
References 35 publications
3
136
0
3
Order By: Relevance
“…6 Autologous MSCs have been investigated for the potential to regenerate a variety of tissues, 20,21 and studies also have confirmed that the use of allogeneic MSCs can efficiently repair bone and other tissue types in different animal models without provoking an adverse immune response. 14,22 In this study, we aimed to increase bone regeneration in the interpremaxillary suture using allogeneic BMSCs. This strategy has two advantages.…”
Section: Discussionmentioning
confidence: 99%
“…6 Autologous MSCs have been investigated for the potential to regenerate a variety of tissues, 20,21 and studies also have confirmed that the use of allogeneic MSCs can efficiently repair bone and other tissue types in different animal models without provoking an adverse immune response. 14,22 In this study, we aimed to increase bone regeneration in the interpremaxillary suture using allogeneic BMSCs. This strategy has two advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that MSCs are effective to treat aGVHD [48][49][50][51][52]. In experimental models MSCs modulate immune system through several mechanisms, including suppression of CD4 + and CD8 + T cell proliferation, induction of regulatory T cells, suppression of B cell differentiation and proliferation, release of soluble immunomodulatory factors and repair of damaged target organs [53][54][55][56][57]. However, little is known about MSCs effects on patients with GVHD.…”
Section: Prevention Of Gvhdmentioning
confidence: 99%
“…The absence of co-stimulatory molecules may lead to tolerance induction instead of rejection of allogeneic MSCs. The absence of host immune response against allogeneic MSCs has been demonstrated in vitro (Bartholomew et al, 2002;Di Nicola et al, 2002;Tse et al, 2003) and in vivo in animals (Atoui et al, 2008;Chen et al, 2009) and humans (Kebriaei et al, 2009;Le Blanc et al, 2004;Prasad et al, 2011;Sundin et al, 2007).…”
Section: Msc Immune Privilegementioning
confidence: 99%